Structural seismic performance of reinforced concrete block system for two storeys safe house - Yip, Chun Chieh (Penerbit UTM Press, 2016)
Severe earthquakes in year 2004 had caused a destructive tsunami and killed more than 170,000 people in Aceh Indonesia. The disaster raises the public awareness and demand in safe house. This paper presented the structural failure behaviour, strength and performance level of two-bays double storeys safe house structure with the scaled of 1:5. Cyclic pushover test was conducted with compliance to the standard guidelines from Federal Emergency Management Agency (FEMA 356) in year 2000. The structural behaviour and deformation patterns under repeated cyclic lateral loads were identified through experimental test. The structural stiffness capacity, performance level, seismic energy dissipation and spectral acceleration of the safe house model were obtained through calculations from the hysteresis curves. Experimental result shows the ultimate lateral load of safe house model was 9.9 kN with roof top displacement of 49.1 mm. The model has performance level of Immediate Occupancy (IO), Life Safety (LS) and Collapse Prevention (CP) at 6.3 mm, 16 mm and 49.1 mm roof top displacement, respectively. It was found that, the safe house structure is able to withstand seismic excitation of 0.98 g spectral acceleration.